THE CURRENT FINANCIAL AND ECONOMIC CRISIS: EMPIRICAL AND METHODOLOGICAL ISSUES - Strachman, Eduardo; Fucidji, José Ricardo (Journal of Advanced Studies in Finance, 2012)
In this paper we describe the main causes of the recent financial crisis as a result of many theoretical, methodological, and practical shortcomings mostly according to heterodox, but also including some important orthodox economists. At theoretical level, there are problems concerning teaching and using economic models with overly unrealistic assumptions. In the methodological front, we find the unsuspected shadow of Milton Friedman’s ‘unrealisticism of assumptions’ thesis lurking behind the construction of this kind of models and the widespread neglect of methodological issues. Of course, the most evident shortcomings are at the practical level: (i) huge interests of the participants in the financial markets (banks, central bankers, regulators, rating agencies mortgage brokers, politicians, governments, executives, economists, etc. mainly in the US, Canada and Europe, but also in Japan and the rest of the world), (ii) in an almost completely free financial and economic market, that is, one (almost) without any regulation or supervision, (iii) decision-taking upon some not well regarded qualities, like irresponsibility, ignorance, and inertia; and (iv) difficulties to understand the current crisis as well as some biases directing economic rescues by governments. Following many others, we propose that we take this episode as an opportunity to reflect on, and hopefully redirect, economic theory and practice.